Investigating the Impact of Leadership Quality and Educational Practices on Student Outcomes through Teacher Attitude and Behavior in Pakistani Educational Institutions: An Applied Science Perspective - Xiang, Wei; Ullah, Muhammad Rizwan (Engineering, Technology & Applied Science Research, 2024)
The present study stresses how leadership quality and educational practices affect student outcomes through the way teacher attitudes and behavior are expressed in Pakistani educational institutions. The quantitative data for this study were collected via random sampling from investors in different cities of Pakistan. A simple random sampling technique was adopted recruiting 1000 teachers from different levels of educational institutions in various areas of Pakistan for data analysis. Therefore, the study considered several factors to ensure that a representative sample, which reflects the large population of Pakistan’s teachers, was taken, allowing for more accurate generalizations based on the study findings. The Partial Least Squares (PLS) method was employed to analyze the data gathered for this study. The latter concluded that educational practices and leadership grades play a significant role in improving student learning. It emphasized the relationship between educational institution management, teachers’ mindsets and actions, and student learning results. These relationships can enhance educational outcomes, leadership development, and teacher preparation. Implications include policy considerations, teacher pedagogical training, leadership skills, and pursuing a more student-centered and holistic educational approach.